Muzyka Ariela i muzyka Kalibana w Burzy Williama Szekspira - Solski, Zbigniew Władysław (Wydawnictwo Naukowe UAM, 2008)
Jan Kott wrote that in Tempest there is Ariel's music and Caliban's music and that there have not been a performance of The Tempest in which there would be no distinction between the two musics. Differentiation of various musics is not only a theatrical trick which serves greater dynamics the reception of the play, but it touches deeper and structural meanings. Opposition between Caliban's music and Ariel's music de facto reveals a clash of a civilisational character. For the culture of Italy rooted in the antiquity and in the "Dionysian" by its primordial character of Ariel’s culture the world of symbolism of Caliban's mother is both distant and alien. Like the witch Sycorax in the role of the queen of the island did not find common grounds with Ariel, neither can her son communicate with Prospero. Between Ariel's music and that of Caliban there is some fissure which makes it difficult to produce the state of mutual balance. On the one hand, harmony, however, unstable can be found in the relations between Prospero and Ariel. Their mutual harmony could be explained by the capability of their cultures to take up cooperation with division of the roles and with a peculiar specialisation. Prospero's "Appolinian", which is manifested in the indirect visual accounts found its complement Ariel's Dionysian culture, which was expressed directly in the recreation, in the musical symbol of the will. Thus, they were not in opposition to each other as elements of contradiction, but rather as two antithetic ways of its removal. While retaining their style, the music of Prospero and that of Ariel found unity in a common source: "the music of spheres*. Was Caliban's inability to enter a dialogue with representatives of other cultures caused by the character of his defiant anti-music? Or just the opposite, the reason is hidden in the dark past, in some hurt the memory of which makes the intercivilisational exchange and cooperation difficult?
Ariel's and Caliban's music in William Shakespeare's The Tempest